Detection of Technical Errors and Construction Optimization for Custom Tissue Arrays at Transplanting and Casting: Zaznavanje tehničnih napak in optimizacija izdelave individualnih tkivnih mrež pri presajanju in vlivanju - Munda, Miha (Acta Medico-Biotechnica, 2021)
Purpose: The purpose of this research is to identify causes for the most common typical defects in the production of tissue arrays at the most crucial stages, and to optimize protocols for custom-made tissue arrays at variable input parameters and different final requirements. In this way, we can avoid difficult repairs of tissue arrays, at which, because of re-allocation, major losses can occur, including destruction of the sample due to mechanical and thermal effects.Methods: Seven hundred and twenty tissue array blocks were included, some for clients and others for experimentation and protocol refinement. Human and animal tissue were used. We tested and evaluated configurations, structural stability, consistency, stability, and practical usability of such designed tissue arrays under different laboratory physical conditions.Results: We recognized and analyzed 12 mistakes in the production of tissue arrays in the histology laboratory during the stages of transplantation and casting. At each examined error we found the causes, gave suggestions for prevention, and provided instructions on how to eliminate or prevent those causes.Conclusion: Problems have solutions that are technically feasible but they require individual adjustments of laboratory procedures, time, and learning. This is more difficult or even impossible for automated laboratories, as in the described handmade tissue arrays. However, all laboratories need to produce with maximum quality and precision, which is possible only with addressing problems regularly. The results of this study will contribute to the optimization of custom made tissue array processes.
Keywords: tissue arrays; construction problems; optimization; histology